UNDERWATER WARP TENSION METER - SIVA DAS, T K (Fishery Technology, 2025)
A self contained electronic solid-state instrument capable ofmeasuring the tension between the different parts of a trawl net inoperation, has been designed and developed for the measurement inthe range 0 to 300 kg with an accuracy of Â± 2 kg. The instrumentis useful for measuring the resistance to motion of various accessoriesof a trawl net. It consists of an inductive type underwater tensiontransducer and an electronic indicating meter kept on. board thevessel, both the units being connected by electric cable.